IJFSNR 2019
DOI: 10.31546/ijfsnr.1005
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Satisfaction of Texture Modified Meals Served in Residential Aged-Care Facilities

Abstract: Food service plays an important role in optimising residential aged care facilities (RACFs) residents' health with mealtime satisfaction a critical component. One third of residents consume texture-modified diets (TMDs). This study investigated satisfaction of TMDs in RACFs collecting documentation audit and interviews with residents and their carers at 12 RACFs. Eating Assessment Tool (EAT-10) and Mini Nutritional Assessment (MNA-SF®) were completed. Inclusion criteria was residents receiving commercially pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…On hospital admission, dementia patients with dysphagia had a higher prevalence of malnutrition and a significantly higher risk of malnutrition compared to those without dysphagia [ 43 ]. Mean MNA-SF scores measured by Miles et al and Vucea et al also indicated the TMD consumers in LTCs were at risk of malnutrition [ 44 , 45 ]. Similar MNA-SF results were found in hospital patients consuming TMDs [ 39 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On hospital admission, dementia patients with dysphagia had a higher prevalence of malnutrition and a significantly higher risk of malnutrition compared to those without dysphagia [ 43 ]. Mean MNA-SF scores measured by Miles et al and Vucea et al also indicated the TMD consumers in LTCs were at risk of malnutrition [ 44 , 45 ]. Similar MNA-SF results were found in hospital patients consuming TMDs [ 39 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of an interview was the most common method for exploring mealtime satisfaction [ 44 , 54 , 55 , 58 ]. Three studies evaluated mealtime satisfaction for shaped/moulded TMDs by survey [ 5 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reason for prescribing TMD is to reduce the risk of choking and prevent aspiration pneumonia. Up to 70 % of institutionalized people may suffer from choking during meals (33). Evidence of symptoms related to swallowing (such as choking) associated with hTMD vs. cTMD is minimal; moreover, results on the effectiveness of TMD to prevent aspiration pneumonia are inconclusive (34,35).…”
Section: Discussionmentioning
confidence: 99%